Permafrost and ground-ice conditions in the Untersee Oasis, Queen Maud Land, East Antarctica - Lacelle, Denis; Verret, Marjolaine; Faucher, Benoit; Fisher, David; Gaudreau, Adam; Pellerin, André; Ecclestone, Miles; Andersen, Dale T. (Antarctic Science, 2024)
Knowledge of Antarctic permafrost is mainly derived from the Antarctic Peninsula and Victoria Land. This study examines the 2019–2023 temperature and humidity conditions, distribution and development of polygonal terrain and the origin of ground ice in soils of the Untersee Oasis. In this region, the surface offset (MAAT ≅ MAGST) and the thermal offset (MAGST ≤ TTIT) reflect the lack of vegetation, absence of persistent snow and a dry soil above the ice table. The mean annual vapour pressure at the ground surface is approximately ~2× higher than in the air but is ~0.67× lower than at the ice table. The size of polygons appears to be in equilibrium with the ice-table depth, and numerical modelling suggests that the depth of the ice table is in turn in equilibrium with the ground surface temperature and humidity. The ground ice at the ice table probably originates from the partial evaporation of snowmelt that infiltrated the dry soil column. As such, the depth of the ice table in this region is set by the water vapour density gradient between the ground surface and the ice-bearing ground, but it is recharged periodically by evaporating snowmelt.
Keywords: Dronning Maud Land; fysisk geografi; geologi; permafrost

Permafrost Hydrogeology of Taylor Valley, Antarctica: Insights From Deep Electrical Resistivity Tomography - Romano, Valentina; Fischanger, Federico; Wilson, Gary; Sciarra, Alessandra; Mazzini, Adriano; Mazzoli, Claudio; Florindo, Fabio; Tartarello, Maria Chiara; Ascani, Massimiliano; Anderson, Jacob; Worthington, Rachel; Hardie, Richard; et al. (Geophysical Research Letters, 2024)
Abstract Global warming has prompted globally widespread permafrost thawing, resulting in enhanced greenhouse gas release into the atmosphere. Studies conducted in the Northern Hemisphere reveal an alarming increase in permafrost thawing. However, similar data from Antarctica are scarce. We conducted a 2-D Deep Electrical Resistivity Tomography (DERT) survey in Taylor Valley, Antarctica, to image the distribution of permafrost, its thicknesses, lower boundaries, and hydrogeology. Results show resistive, discontinuous domains that we suggest represent permafrost units. We also find highly conductive layers (5?10 Ω·m), between 300?350 m and 600?650 m below ground level and a shallower (?50?100 m depth) conductive layer. The combined data set reveals a broad brine system in Taylor Valley, implying multi-tiered groundwater circulation: a shallow, localized system linked with surface water bodies and a separate deeper, regional circulation system. The arrangement of these brines across different levels, coupled with the uneven permafrost distribution, underscores potential interplay between the two systems.
Keywords: Antarktis; geologi; global oppvarming; hydrogeologi; klimaendringer; permafrost